FORMALLY STRUCTURAL MODELING OF ECONOMIC SYSTEMS - Ilman, O. V.; Ilman, V. M. (Science and Transport Progress, 2006)
For modelling economic systems, it has been proposed to use a model of formal structure systems, which has the property of formal system, algebra and structure (composition). An example of the modelling of a bookkeeping system has been considered.